Porcine feasibility and safety study of a new paclitaxel-eluting biliary stent with a Pluronic-containing membrane - Jang, S. I.; Kim, J.-H.; Kim, M.; Yang, S.; Jo, E. A.; Lee, J. W.; Na, K.; Kim, J. M.; Jeong, S.; Lee, D. H.; Lee, D. K. (Endoscopy, 2012)
Background and study aim: Metal stents for malignant biliary obstruction are susceptible to occlusion by tumor ingrowth or overgrowth. Therefore, we previously reported our use of a metal stent covered with a paclitaxel-incorporated membrane giving an antitumor effect to prevent occlusion from tumor ingrowth. We have also developed a new generation of paclitaxel-eluting biliary stent using a membrane containing Pluronic F-127 for effective drug delivery. The aim of this study was to investigate the safety and efficacy of drug delivery for this newly developed stent in the biliary tract. Methods: Metal stents were coated with paclitaxel and various concentrations of Pluronic F-127 in phosphate-buffered saline solution. Stents containing varying concentrations were placed in the bile ducts of eight pigs divided as follows: group I, 0 % Pluronic + 0 % paclitaxel; group II, 0 % Pluronic + 10 % paclitaxel; group III, 10 % Pluronic + 10 % paclitaxel; group IV, 20 % Pluronic + 10 % paclitaxel. The histology of the porcine bile duct and the amount of paclitaxel in the porcine serum were examined. The amount of paclitaxel released was also measured in vitro.Results: Histologic changes in the porcine biliary epithelium were acceptable in terms of safety, based on inflammatory cell infiltration and fibrotic reaction. No significant differences in histology were observed between the groups. In the porcine serum analysis, released paclitaxel was detected for 28 days with the 10 % Pluronic concentration (group III). However, released paclitaxel was observed for only 7 days in groups II and IV. In the in vitro experiments, long-lasting release of paclitaxel was also noted from the stent with 10 % Pluronic.Conclusions: The new paclitaxel-eluting stent with 10 % Pluronic F-127 is safe and provides enhanced local drug delivery.